The Perspective and the Effects of Robotics Courses in School Education - Ana-Maria Popa (National Centre for Policy and Evaluation in Education, 2019)
This research has focused on exploring how the introduction of robotics classes in school can improve the educational process, especially in the direction of teaching children with the abilities of the 21st century, due to the new robotics that are attracting more and more. Two groups of students from a state school in Bucharest, Secondary School Nr. 195, participated in this research. The experimental group participated in the Robotics course and the control group participated in a course on Applied Mathematics in Transmission of the Movement, over a seven weeks period, in the year 2017. At that time, the students in both groups were in 3rd grade, their average ages was 9-10 years. The group that conducted the Robotics course had 33 students, and the group that developed the Applied Mathematics course in Transmitting the Movement had 37 students. For this research, LEGO kits such as Lego Mindstorm have been used and assimilated, allowing students to work in teams. This facilitated the understanding of the basic notions, and the children subsequently succeeded in expressing and developing their own ideas. The notions of robotics, the basic technological concepts have been easily assimilated by groups of students aged 10. Student debates, mathematical problem solving, teamwork, and the interest of children in the process of designing robots shows that robotics is a winning discipline.